(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
This paper aims to propose an analysis of racism in the socio-historical formation of western modernity and contemporary capitalist societies. For this, we start from Frantz Fanon’s contributions to point out the sociogenesis of racialized subjects as a determining factor of the economic and psychological structure of colonialism. Along with this, we portray the different claims of Fanon’s thought in the critique of modernity, focusing on decolonial grammars, to think about the formation of non-being under the Latin American locus. We conclude the writing by pointing to the relevance of the intersections of Fanonian thought and decoloniality for a critical-structural perspective of racism in contemporary times. Keywords: Frantz Fanon. Sociogenesis. Decolonial thinking. Epistemologies of the damned.